2010
DOI: 10.2215/cjn.07371009
|View full text |Cite
|
Sign up to set email alerts
|

Increased Incidence of Angioedema with ACE Inhibitors in Combination with mTOR Inhibitors in Kidney Transplant Recipients

Abstract: Background and objective: The clinical manifestation of angioedema ranges from minor facial edema up to life-threatening swelling of mouth and throat. Hereditary defects, drugs, and food allergies may play a role in the development of angioedema. We systematically investigated the incidence of angioedema in renal allograft recipients treated with mTOR inhibitors (mTORis).Design, setting, participants, & measurements: All patients in the authors' electronic database who had received mTORis (n ‫؍‬ 309) between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 20 publications
(26 reference statements)
4
40
0
5
Order By: Relevance
“…No data are available regarding the treatment of choice for hypertension, regarding neither the incidence of proteinuria nor the effect of long-term use of ACEi in TSC. However, we would like to highlight the increased incidence of angioedema in patients treated with the combination of ACEi and mTORi [50]. This needs to be further elucidated in a large TSC cohort.…”
Section: Renal Outcomementioning
confidence: 93%
See 1 more Smart Citation
“…No data are available regarding the treatment of choice for hypertension, regarding neither the incidence of proteinuria nor the effect of long-term use of ACEi in TSC. However, we would like to highlight the increased incidence of angioedema in patients treated with the combination of ACEi and mTORi [50]. This needs to be further elucidated in a large TSC cohort.…”
Section: Renal Outcomementioning
confidence: 93%
“…However, the combination of treatment with ACEi and mTORi should be avoided. Duerr et al reported a higher incidence of angioedema under combined therapy with mTORi and ACEi in kidney transplant recipients [50]. There is no recommendation on the evaluation of proteinuria.…”
Section: Recommendations For the Surveillance Of Tsc Patientsmentioning
confidence: 99%
“…The excess risk of angioedema (ranging from minor facial edema up to lifethreatening throat and mouth swelling) associated with mTOR and ACE inhibitor combination therapy could be explained by defective degradation of the vasoactive peptides bradykinin or substance P when ACE is inhibited (20,21). Bradykinin is inactivated by aminopeptidase P (22), whereas substance P is inactivated by dipeptidyl peptidase IV (23).…”
Section: Safetymentioning
confidence: 99%
“…Although not definitively demonstrated in humans, one hypothesis is that immunosuppressive agents increase this risk by decreasing the activity of circulating dipeptidyl peptidase IV (both dipeptidyl peptidase IV and ACE inactivate vasodilatory bradykinin and substance P). This effect is seen with both calcineurin and mTOR inhibitors but is greater with the latter 2, 8. Reports have demonstrated episodes of facial and sublingual angioedema in kidney transplant patients on mTOR inhibitors without concomitant use of an ACE‐inhibitor 4, 9.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the increasing incidence of ACE inhibitor‐induced angioedema in patients taking calcineurin inhibitors,2, 3, 4, 5, 6, 7, 8, 9 extrapolation of basic science studies suggests that mTOR inhibitors pose a greater risk to interact with ACE inhibitors. Physicians prescribing mTOR inhibitors should have knowledge of the potential interaction.…”
Section: Discussionmentioning
confidence: 99%